2014
DOI: 10.1159/000362792
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive Medication Adherence in Kidney Transplant Patients

Abstract: Objectives: To assess the degree of immunosuppressive medication adherence in kidney transplant patients (KTPs) and to determine if there is a difference in the rate of adherence to tacrolimus (Tac), cyclosporine (CsA) and sirolimus (Sir). Subjects and Methods: From a total of 63 KTPs treated at the Clinic of Nephrology, Clinical Centre Niš, Serbia, 60 participated in the study by responding to questionnaires. They were divided into the adherence group (n = 43) and the nonadherence group (n = 17) according to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
(27 reference statements)
3
10
0
5
Order By: Relevance
“…Liu et al [16] found self-reported NA to be associated with serum concentration fluctuation for tacrolimus but not cyclosporine. Similar results were found by Lalic et al [35], while other studies found no correlation at all between self-reports and IS trough levels [10,34]. Equally, no associations were detected between collateral reports and self-reports [11,34,36], nor between physicians' estimates and the variability of trough levels [11,34].…”
Section: Introductionsupporting
confidence: 87%
“…Liu et al [16] found self-reported NA to be associated with serum concentration fluctuation for tacrolimus but not cyclosporine. Similar results were found by Lalic et al [35], while other studies found no correlation at all between self-reports and IS trough levels [10,34]. Equally, no associations were detected between collateral reports and self-reports [11,34,36], nor between physicians' estimates and the variability of trough levels [11,34].…”
Section: Introductionsupporting
confidence: 87%
“…Longer term outcomes are important to patients and clinicians and may provide better insight into the effect of alternative CNI strategies. Inconsistent reporting of patient adherence is another limitation, and noncompliance may account for inferior outcomes observed . Most important, the majority of studies that we reviewed were conducted in patients with low or average risk, and our findings may not be applicable to patients at higher risk.…”
Section: Discussionmentioning
confidence: 87%
“…The service model used was pharmacotherapy follow-up, in line with an adaptation of the Dader method. 17 , 18 The pharmacist consultation was carried out in a day-hospital or in the outpatient Hematology Clinic according to the patient´s needs. The first meeting between pharmacist and patient was always on the first day after discharge from an isolated ward.…”
Section: Methodsmentioning
confidence: 99%